Research Trends in Science Learning Using a Gamification Approach to Enhance Students' Critical, Creative Thinking, and Problem-Solving Skills: A Systematic Literature Review - Muhamad Hendri Diarta; Nanda Aulia Pratiwi (Indonesian Journal of STEM Education, 2025)
Gamification is an innovative approach that can enhance students’ motivation, active participation, and meaningful learning experiences. This study aims to describe research trends in science learning that employ gamification to improve students’ creative thinking and problem-solving skills. The study adopts a systematic literature review approach, analyzing a total of 270 publications. Articles from the past ten years were selected based on inclusion criteria that covered the use of gamification in science learning contexts, the measurement of creative thinking or problem-solving abilities, and publication in reputable journals. The results indicate that research trends on gamification in science education have increased significantly, with a shift in focus from merely applying game elements to examining more specific pedagogical effects on higher-order thinking skills. Gamification has been shown to enhance learning engagement and facilitate the development of creativity and problem-solving abilities through challenge-based activities, simulations, and exploration. Furthermore, the use of digital platforms as a medium for integrating gamification reflects the transformation of science learning toward more interactive and technology-adaptive approaches.